Method for producing geopolymer composition and method for producing geopolymer cured product

By blowing carbon dioxide gas into the geopolymer slurry for carbonization, the problems of short serviceability and large environmental load in the prior art have been solved, and the effects of high strength expressivity and low environmental load are achieved.

CN119698399APending Publication Date: 2025-03-25TOKUYAMA CORP

Patent Information

Application Number
CN202380059431.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-26
Filing Date
2023-09-22
Publication Date
2025-03-25

Smart Images

  • Figure BDA0005269314370000131
    Figure BDA0005269314370000131
  • Figure BDA0005269314370000141
    Figure BDA0005269314370000141
Patent Text Reader

Abstract

A method for producing a geopolymer composition, the method comprising: (1) a first step for carbonating a fine slag powder by blowing carbon dioxide gas into a slurry containing fine slag powder and water to adjust the pH of the slurry to 6.0-12.0; and a second step for mixing the slurry containing the carbonated fine slag powder obtained in the first step, fly ash, and an alkali metal salt, or the method comprises: (2) a first step for carbonating the fine slag powder by blowing carbon dioxide gas into a slurry containing the fine slag powder, fly ash, and water to adjust the pH of the slurry to 6.0-12.0; and a second step for mixing the slurry containing the carbonated fine slag powder obtained in the first step with an alkali metal salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a setting delay technology for geopolymers. Background Art

[0002] Geopolymer is defined as "a material obtained by solidifying a raw material mainly composed of amorphous aluminum silicate (active filler) and at least one aqueous solution of alkali metal silicates, carbonates, and hydroxides (alkali source) without using cement clinker." It has attracted attention as a building material that has low CO2 emissions during manufacturing compared to cement solids and has excellent acid resistance, heat resistance, etc.

[0003] In recent years, in order to improve the strength performance of geopolymers at room temperature, slag powder has been used in addition to fly ash as an active filler. However, since slag powder is used as an active filler, the usable time (setting time) of the geopolymer is shortened to about 15 to 40 minutes, resulting in a major disadvantage that sufficient time cannot be ensured for transportation and pouring operations.

[0004] Therefore, Patent Document 1 discloses a method for producing a geopolymer composition having excellent usable life and initial strength, which comprises: a process of obtaining carbonated slag powder in an atmosphere with a carbon dioxide concentration of 1% or more; and a process of mixing the carbonated slag powder with an alkali source and fly ash.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-54678 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] The method for producing geopolymers described in Patent Document 1 performs carbonation treatment of slag powder while maintaining high temperature and constant humidity for a maximum of 30 days, and requires drying treatment after carbonation treatment, so the productivity is very low and the energy consumption is also large, so it is considered to be a method with a large environmental load. Based on the above, there is no disclosed technology that can maintain the strength performance of geopolymers and extend the usable time, short time, simple and low environmental load.

[0010] The present invention has been made based on the above circumstances, and an object of the present invention is to provide a method for producing a geopolymer composition in a short time, simply and with low environmental load, while maintaining strength development and having a usable time sufficient for work.

[0011] Solutions for solving problems

[0012] The inventors of the present invention have repeatedly conducted in-depth research to easily obtain a geopolymer composition that maintains strength performance and has a usable time sufficient for operation in a short period of time. As a result, they found that by setting up a process of blowing carbon dioxide gas into slag powder and slurry while performing carbonation treatment until a specified pH is reached, the effect of extending the usable time (setting time) of the geopolymer can be easily obtained in a short period of time without imposing a large load on the environment.

[0013] That is, the first present invention is a method for producing a geopolymer composition, which is a method for producing a geopolymer composition containing slag powder, fly ash and an alkali metal salt.

[0014] It has the following processes:

[0015] (1) a first step of blowing carbon dioxide gas into a slurry containing slag powder and water to adjust the pH of the slurry to 6.0 to 12.0, thereby carbonating the slag powder; and a second step of mixing the slurry containing the carbonated slag powder obtained in the first step, fly ash, and an alkali metal salt,

[0016] Alternatively, it has the following steps:

[0017] (2) a first step of blowing carbon dioxide gas into a slurry comprising slag powder, fly ash and water to adjust the pH of the slurry to 6.0 to 12.0, thereby subjecting the slag powder to carbonation treatment; and a second step of mixing the slurry comprising the carbonation-treated slag powder obtained in the first step with an alkali metal salt.

[0018] The pH of the slurry is preferably adjusted to 6.5 to 7.5 in the first step. In addition, the treatments of the first step and the second step are preferably performed at a construction site where the geopolymer composition is cured.

[0019] The second present invention is a method for producing a geopolymer cured product, wherein after obtaining a geopolymer composition by the aforementioned production method, the obtained geopolymer composition is cured at a temperature range of 5°C to 90°C. The geopolymer composition is characterized in that the strength performance at room temperature (5°C to 35°C) is high.

[0020] It should be noted that the alkali metal salt preferably includes an alkali silicate powder and an alkali carbonate powder. The alkali metal silicate powder is more preferably a sodium silicate powder, and the alkali metal carbonate powder is more preferably a sodium carbonate powder. Furthermore, it is preferred that the alkali metal silicate powder is a sodium silicate powder, and the alkali metal carbonate powder is a sodium carbonate powder.

[0021] Effects of the Invention

[0022] A method for producing a geopolymer composition in which the carbonation-treated slag powder is directly used as a slurry is provided by providing a step of carbonation treatment of the slag powder by blowing carbon dioxide gas into a slurry containing slag powder and water to obtain a predetermined pH, thereby obtaining a geopolymer composition having a sufficient usable time (setting time) and high strength performance for construction work. Furthermore, the production method of the present invention can be implemented at a construction site using conventional geopolymer materials and a known mixing device, and therefore has the advantages of simplicity and low environmental load. DETAILED DESCRIPTION

[0023] Hereinafter, an embodiment of the present invention will be described in detail, but the present invention is not limited to the embodiment. It should be noted that "part" and "%" in the present specification are based on mass unless otherwise specified.

[0024] <Method for producing geopolymer composition>

[0025] The method for producing a geopolymer composition of the present invention comprises a first step and a second step.

[0026] The present invention is a method for producing a geopolymer composition, which is a method for producing a geopolymer composition comprising carbonated slag powder, fly ash and an alkali metal salt, and comprises the following steps:

[0027] (1) a first step of blowing carbon dioxide gas into a slurry containing slag powder and water to adjust the pH of the slurry to 6.0 to 12.0 to carbonate the slag powder; and a second step of mixing the slurry containing the carbonated slag powder obtained in the first step, fly ash and an alkali metal salt, or the method comprises the following steps:

[0028] (2) a first step of blowing carbon dioxide gas into a slurry comprising slag powder, fly ash and water to adjust the pH of the slurry to 6.0 to 12.0, thereby subjecting the slag powder to carbonation treatment; and a second step of mixing the slurry comprising the carbonation-treated slag powder obtained in the first step with an alkali metal salt.

[0029] Hereinafter, the method for producing a geopolymer composition comprising (1) a first step of blowing carbon dioxide gas into a slurry comprising slag powder and water to adjust the pH of the slurry to 6.0 to 12.0, and subjecting the slag powder to carbonation treatment; and (2) a second step of mixing the slurry comprising the carbonated slag powder obtained in the first step, fly ash and an alkali metal salt with the slurry comprising the carbonated slag powder, fly ash and water, and subjecting the slurry to carbonation treatment; and (3) a second step of mixing the slurry comprising the carbonated slag powder obtained in the first step and a geopolymer composition with an alkali metal salt, and subjecting the slurry to carbonation treatment. Hereinafter, the method for producing a geopolymer composition comprising (1) a first step of blowing carbon dioxide gas into a slurry comprising the slurry comprising the carbonated slag powder, fly ash and water, and subjecting the slurry to carbonation treatment; and (4) a second step of mixing the slurry comprising the carbonated slag powder obtained in the first step and a geopolymer composition with an alkali metal salt, and subjecting the slurry to carbonation treatment.

[0030] The difference between the manufacturing method (1) and the manufacturing method (2) is whether fly ash is added in the first step as a necessary condition or in the second step as a necessary condition. In the manufacturing method (1), fly ash must be added in the second step, and in the manufacturing method (2), fly ash must be added in the first step. It should be noted that in any manufacturing method, fly ash can be added in both the first step and the second step. That is, in the manufacturing method (1), fly ash can be added in the first step in addition to the second step, and in the manufacturing method (2), fly ash can be added in the second step in addition to the first step.

[0031] First, the production method (1) will be described.

[0032] (1st step)

[0033] In the first step of the production method (1), carbon dioxide gas is blown into a slurry containing slag fine powder and water to adjust the pH of the slurry to 6.0 to 12.0, thereby subjecting the slag fine powder to carbonation treatment.

[0034] (Slag powder)

[0035] Slag powder is produced when pig iron is generated, and contains CaO, SiO2, Al2O3, and MgO as main components. As slag powder, for example, slag powder containing 20% ​​by mass or more and 60% by mass or less of calcium in terms of calcium oxide (CaO) can be cited. In addition, the type of slag is not particularly limited, and it can be any one of blast furnace slag and steelmaking slag. From the viewpoint of reactivity, blast furnace slag is preferably used. In particular, from the viewpoint of strength performance and shrinkage at room temperature of the geopolymer solidified product manufactured using the obtained geopolymer composition, it is more preferable to use blast furnace slag powder 4000 for concrete specified in JIS A 6206.

[0036] (water)

[0037] The water is not particularly limited, and tap water, ion-exchanged water, pure water, etc. can be used.

[0038] (Carbon dioxide gas)

[0039] Carbon dioxide gas does not need to be a gas of 100% carbon dioxide, and can be a gas containing a certain amount of carbon dioxide. And then, by using the combustion waste gas of cement kiln, the extracted gas of chlorine bypass, the combustion waste gas of general thermal power plant, the combustion waste gas of biomass incineration equipment, the combustion waste gas of biomass power plant, the exhaust gas of automobile (concrete mixer truck) etc., the carbon dioxide contained in these gases can be fixed in the form of calcium carbonate, so the reduction effect of carbon dioxide discharge can also be expected. The carbon dioxide concentration in carbon dioxide gas is more than 10 mass %, and from the aspect that can shorten the carbonation treatment time, it is preferably more than 50 mass %. It should be noted that the combustion waste gas of general thermal power plant is about 15 mass %, and the combustion waste gas of cement kiln, the extracted gas of chlorine bypass are 20 mass %~30 mass %.

[0040] (Carbonation treatment)

[0041] It is preferred that the slurry containing the slag fine powder and water is uniformly mixed by a stirrer or the like while carbon dioxide gas is blown into the slurry to perform carbonation treatment on the slag fine powder.

[0042] For the slurry comprising slag powder and water, the above-mentioned slag powder and water are added to a container, uniformly mixed using a stirrer or the like, and a slurry is prepared. The amount of water may be the total amount used for the geopolymer composition, or may be a part thereof. The mass ratio of water to the slag powder is more than 0.4, preferably from the viewpoint of easily and uniformly stirring the slurry. By blowing carbon dioxide in the slurry state and bubbling, it is possible to carry out the desired carbonation treatment in a short time. It should be noted that in the slurry comprising slag powder and water, in addition to the slag powder, other components commonly used in the geopolymer composition may be included within the scope of not impairing the effect of the present invention.

[0043] The mixer is not particularly limited as long as it is a known stirring device or kneading device used for kneading mortar or concrete, and for example, a hand mixer, a Hobart mixer, etc. can be used.

[0044] The blowing of carbon dioxide gas is carried out until the pH of the slurry becomes 6.0 to 12.0. When the pH is less than 6.0, the strength performance at room temperature is reduced. In addition, if the pH exceeds 12.0, sufficient usable time for construction work cannot be obtained. Therefore, from the perspective of being able to maintain the initial strength performance of the geopolymer solidified material and ensuring sufficient usable time for construction work, it is preferred to make the slurry pH 6.5 to 7.5, and more preferably 6.5 to 7.0. The slurry containing slag powder and water before blowing carbon dioxide gas is usually about pH 12.5, and the pH is reduced by blowing carbon dioxide gas. In addition, by blowing carbon dioxide gas, the calcium component dissolved from the slag powder into the slurry is captured and changed into inactive calcium carbonate, thereby fixing carbon dioxide, and the rapid reaction of alkali metal silicate and calcium component is suppressed, which can extend the usable time (solidification time) and obtain sufficient usable time for construction work.

[0045] When the carbonation treatment of the slag fine powder is performed, the slurry temperature is preferably 5° C. to 60° C. from the viewpoint of the solubility of carbon dioxide in water and the dissolution of calcium ions derived from the slag fine powder.

[0046] When the carbon dioxide gas is combustion exhaust gas, the carbon dioxide gas can be transferred from the gas discharge device by using a pipe, etc., so that the carbonation treatment can be performed not only near the gas discharge device but also at a place far from the gas discharge device. In addition, the carbon dioxide gas can be blown into the slurry by inserting a pipe or a hose into the slurry.

[0047] The pH can be measured using a known measuring device, and it is particularly preferred to use a measuring device for a high concentration suspension. The pH measurement can be carried out by directly inserting a pH electrode into the slurry. The pH measurement can be carried out continuously from the beginning of the treatment, as long as carbon dioxide gas is blown in until a specified pH is reached. The blowing time can be set to a short time of about 10 to 25 minutes by adjusting the carbon dioxide concentration and flow rate in the carbon dioxide gas used, which can be easily implemented at the construction site.

[0048] (Second step)

[0049] In the second step of the production method (1), the slurry containing the carbonation-treated slag fine powder obtained in the first step, fly ash and an alkali metal salt are mixed to obtain a geopolymer composition.

[0050] The mixing of the slurry comprising the carbonation-treated slag powder obtained by the first process, fly ash and alkali metal salt can be continued in the container used in the carbonation treatment of the first process, or can be carried out using other containers. By continuously carrying out the first process and the second process in the same container, the operation can be simplified and poor mixing can be alleviated, so it is preferred to continuously carry out the first process and the second process in the same container. In this case, while stirring the slurry comprising the carbonation-treated slag powder obtained by the first process, fly ash and alkali metal salt are added to mix. There is no restriction on the order of adding fly ash and alkali metal salt. The mixing device is not particularly limited and can be the same as or different from the first process, and examples thereof include a forced twin-shaft mixer, a Hobart mixer, a manual mixer, etc.

[0051] When the first step and the second step are performed in different containers, there is no restriction on the order in which the slurry containing carbonation-treated slag powder obtained by the first step, fly ash and alkali metal salt are added to the container in the second step. However, from the aspect of sufficient mixing, it is preferred to add fly ash and alkali metal salt to the slurry containing carbonation-treated slag powder obtained by the first step. There is no restriction on the order in which fly ash and alkali metal salt are added. The mixing device is not particularly limited, and examples thereof include a forced twin-shaft mixer, a Hobart mixer, a manual mixer and the like.

[0052] (Fly ash)

[0053] Fly ash is fine ash recovered from exhaust gas by a dust collector in the coal ash produced as a by-product of coal combustion by burning finely pulverized coal in a boiler of a coal-fired power plant or the like. It is mainly composed of SiO2 and Al2O3, and is classified into types I to IV based on particle size and flow value in JIS A6201. The standard of fly ash is not particularly limited, but preferably type I and type II, which have fine particle size and are highly reactive. In addition, the free lime contained in the fly ash reacts rapidly with the alkali metal silicate, which is the main reason for shortening the usable time (setting time). Therefore, when using fly ash with a high free lime content, the effect of the present invention can be further exerted. The free lime content of the fly ash is usually less than 0.1% by mass, but in the method of the present invention, it can be used without problem even if it is 0.1% by mass or more, it can be used without problem even if it is 0.5% by mass or more, and it can be used without problem even if it is 1.0% by mass or more.

[0054] The content of fly ash relative to the total mass of fly ash and slag powder is preferably 50 to 90% by mass, more preferably 60 to 85% by mass. When the content is 50% by mass or more, when the geopolymer composition is mixed with water, it is also preferred from the viewpoint of being able to maintain good fluidity, being easy to obtain sufficient workability, and expanding the effective utilization of fly ash. In addition, when the content is 90% by mass or less, good strength performance of the geopolymer composition cured product is obtained in the initial age.

[0055] (Alkali Metal Salt)

[0056] Alkali metal salts are salts containing alkali metal ions (Li + 、Na + , K + Alkali metal salts include salts of alkali metal silicates and alkali metal carbonates. In view of low heat of dissolution, no adverse effect on the mixing process, and the ability to obtain a geopolymer composition solidified product with excellent compressive strength by curing at room temperature, it is preferred to use alkali metal silicates and alkali metal carbonates in combination. The alkali metal salt may be in the form of a liquid or a powder, and may be an anhydrous salt, a hydrate, or an aqueous solution. In view of high transportability and workability, a powder is preferred.

[0057] Here, in the conventional methods, aqueous solutions of alkali metal silicates and alkali metal hydroxides are generally used (for example, refer to paragraph

[0002] of Patent Document 1), which are difficult to transport to the construction site in the form of aqueous solutions, and even if the alkali metal hydroxide powder (solid) is used, the heat release when dissolved in the solution is large, so it is difficult to perform appropriate kneading at the construction site and it is difficult to ensure the physical properties of the manufactured composition. On the other hand, in the method of the present invention, by using alkali metal carbonate powder with low heat release, kneading at the construction site can be easily performed as in the past, so that the geopolymer composition can be appropriately manufactured at the construction site.

[0058] (Alkali Metal Silicate)

[0059] As described above, the alkali metal silicate is preferably in the form of a powder from the viewpoint of high transportability and workability.

[0060] As the alkali metal silicate powder, there can be listed sodium silicate powder (SiO2 / NaO2 molar ratio: about 1.95 to 3.4), sodium metasilicate powder (one type, two types), potassium silicate powder, potassium metasilicate powder, lithium silicate powder, etc. From the perspective of excellent strength performance and durability and being a relatively inexpensive powder material, sodium silicate powder (SiO2 / NaO2 molar ratio: about 1.950 to 2.2, H2O=about 20 mass%) is preferred.

[0061] (Alkali Metal Carbonate)

[0062] As described above, the alkali metal carbonate is preferably in the form of a powder from the viewpoint of high transportability and workability.

[0063] Examples of alkali metal carbonate powders include sodium carbonate (Na2CO3), potassium carbonate (K2CO3) and lithium carbonate (Li2CO3). Sodium carbonate powder is preferred because it is relatively inexpensive and highly reactive with slag fine powder.

[0064] The molar ratio Si / AL of silicon (Si) contained in the alkali metal silicate constituting the alkali metal salt to the alkali metal element (AL) contained in the alkali metal salt is preferably 0.05 to 0.85. By setting Si / AL to 0.05 or more, the compressive strength of the geopolymer cured product can be ensured even at room temperature, and by setting Si / AL to 0.85 or less, the fluidity of the geopolymer composition that is easy to use for on-site operations can be ensured. From the above-mentioned aspects, Si / AL is more preferably 0.2 to 0.75.

[0065] The molar ratio AL / W of the alkali metal element (AL) to water (W) constituting the alkali metal salt is preferably 0.05 to 0.3. By setting AL / W to be greater than 0.05, the compressive strength of the geopolymer solidified material can be ensured even at room temperature, and by setting AL / W to be less than 0.3, the fluidity of the geopolymer composition for easy on-site operations can be ensured. From the above viewpoints, AL / W is more preferably 0.05 to 0.18, and further preferably 0.08 to 0.12. In addition, the alkali metal salt may be a single object or may be added in the form of an aqueous solution. When the alkali metal salt is added in the form of an aqueous solution, the difference between the total amount of water contained in the mixing (blending) and the amount of water in the aqueous solution of the alkali metal salt is taken as the amount of water used in the first step.

[0066] Next, the production method (2) will be described.

[0067] It should be noted that the slag powder, fly ash, water, carbon dioxide gas, and alkali metal salt used in the production method (2) are the same as the slag powder, fly ash, water, carbon dioxide gas, and alkali metal salt used in the production method (1).

[0068] (1st step)

[0069] In the first step of the production method (2), carbon dioxide gas is blown into a slurry containing slag powder, fly ash and water to adjust the pH of the slurry to 6.0 to 12.0, thereby subjecting the slag powder to carbonation treatment.

[0070] (Carbonation treatment)

[0071] The carbonation treatment in the first step of the production method (2) may be carried out in the same manner as in the first step of the production method (1), except that fly ash is added in addition to the slag fine powder.

[0072] When the calcium content of fly ash is high, by adding fly ash in addition to slag powder, the calcium component eluted from the fly ash into the slurry is captured and converted into inactive calcium carbonate, thereby making it possible to fix carbon dioxide. In addition, the rapid reaction of the calcium component derived from the fly ash with the alkali metal silicate is suppressed, thereby preventing the shortening of the usable time due to the calcium component derived from the fly ash.

[0073] When preparing the slurry containing slag powder, fly ash and water, the order of adding the components is not limited.

[0074] The content of fly ash relative to the total mass of fly ash and slag powder is preferably 50 to 90 mass %, more preferably 60 to 85 mass %, as in the manufacturing method (1). By being 50 mass % or more, when a geopolymer composition is prepared, it is also preferred from the viewpoint of being able to maintain good fluidity, being easy to obtain sufficient workability, and expanding the effective utilization of fly ash. In addition, by being 90 mass % or less, good strength performance of the geopolymer composition cured product is obtained in the initial age.

[0075] The amount of water may be the total amount used for the geopolymer composition as in the manufacturing method (1), or may be a part thereof. The mass ratio of water to slag powder and fly ash is 0.4 or more, which is preferred from the viewpoint of easy and uniform stirring of the slurry. It should be noted that in the slurry comprising slag powder, fly ash and water, in addition to slag powder and fly ash, other components commonly used in geopolymer compositions may be included within the range that does not impair the effects of the present invention.

[0076] (Second step)

[0077] In the second step of the production method (2), the slurry containing the carbonation-treated slag fine powder obtained in the first step is mixed with an alkali metal salt to obtain a geopolymer composition.

[0078] The mixing of the slurry containing the carbonation-treated slag fine powder obtained by the first step and the alkali metal salt can be carried out in the same manner as the second step of the manufacturing method (1) except that no fly ash is added. The mixing can be continued in the container used for the carbonation treatment in the first step, or in another container. It is preferred that the first and second steps are carried out continuously in the same container.

[0079] (Mixing process)

[0080] In the method for producing the geopolymer composition of the present invention, a mixing step is provided after the second step in which a predetermined amount of admixtures, additives, aggregates, etc. are mixed simultaneously or sequentially and mixed using a mixing device. As admixtures and additives, known materials used in concrete such as fluidizers, shrinkage reducers, rust inhibitors, waterproof materials, retarders, defoamers, dust suppressants, pigments, and calcium carbonate powder can be listed. As aggregates, known aggregates used in concrete such as light aggregates, ordinary aggregates, heavy aggregates, limestone aggregates, slag aggregates, and silica sand can be listed. The mixing device is not particularly limited, and examples thereof include a forced twin-shaft mixer for mixing concrete.

[0081] By continuously carrying out the second step and the mixing step in the same mixing device, the operation can be simplified and poor mixing can be alleviated. Furthermore, the first step to the mixing step can also be continuously carried out in the same mixing device. The mixing device is not particularly limited, and for example, a forced twin-shaft mixer, a Hobart mixer, a manual mixer, etc. can be listed.

[0082] <Method for producing geopolymer solidified material>

[0083] The method for producing a geopolymer cured product of the present invention comprises a casting step and a curing step in addition to the first step, the second step and the kneading step as the method for producing a geopolymer composition.

[0084] The method for producing a geopolymer solidified product of the present invention comprises obtaining a geopolymer composition by the above-mentioned method of the present invention and then curing the obtained geopolymer composition at a temperature ranging from 5°C to 90°C.

[0085] The geopolymer composition obtained by the above-mentioned production method may be poured and then cured to obtain a geopolymer cured product.

[0086] (Pouring process)

[0087] In the casting process, the geopolymer composition obtained by the method for producing a geopolymer composition of the present invention is placed in a mold frame and compacted preferably by a known compaction method, thereby obtaining a dense geopolymer cured product.

[0088] (Maintenance process)

[0089] In the curing process, after the pouring process, by curing the geopolymer composition at a temperature range of 5°C to 90°C, a geopolymer cured product as a cured product of the geopolymer composition can be obtained. In particular, when an alkaline silicate and an alkaline carbonate are used in the geopolymer composition, a geopolymer cured product having excellent compressive strength can be obtained by curing at a normal temperature of 5 to 35°C. Other curing conditions are not particularly limited, and may be curing conditions commonly used. For example, steam curing, sealed curing, curing in air, curing in water, etc. are used.

[0090] According to the method for manufacturing a geopolymer composition of the present invention, a geopolymer composition having sufficient strength performance and usable time for construction can be obtained in a short time. Furthermore, since the method for manufacturing the geopolymer composition can be implemented at the construction site using conventional geopolymer materials and known mixing devices, it is not necessary to specially prepare machines and materials for the carbonation treatment of slag powder. In addition, during the carbonation treatment of slag powder, carbonates are formed with calcium, magnesium, etc. in the slurry of slag powder. Thus, there is the advantage of being able to achieve the fixation and effective utilization of CO2 as a greenhouse gas. In addition, the CO2 gas used in carbon dioxide can contain a certain amount of CO2 such as industrial waste gas. Therefore, the geopolymer solidified material obtained using the geopolymer composition obtained by the method for manufacturing a geopolymer composition of the present invention has a low environmental load compared with conventional geopolymer compositions, and can replace cement compositions as a binder for concrete for various purposes.

[0091] <Other Implementation Methods>

[0092] It should be noted that the method for producing the geopolymer composition and the method for producing the geopolymer cured product of the present invention are not limited to the above-mentioned embodiments, and various changes can be made within the scope of the present invention. Furthermore, a part of the structure of a certain embodiment can be deleted. In addition, known techniques can be added to the structure of a certain embodiment.

[0093] Example

[0094] The present invention is described in further detail below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Various modifications and application examples are also included in the present invention as long as the advantages of the present invention are not greatly impaired.

[0095] (raw materials)

[0096] (1) Fly ash (FA): Fly ash type II (according to JIS A 6201, free lime about 0.1 mass%)

[0097] (2) Slag fine powder (BFS): Blast furnace slag fine powder 4000 (according to JIS A 6206)

[0098] Alkali metal salts (alkali metal silicate powder, alkali metal carbonate powder)

[0099] (3) Powdered sodium silicate: Sodium silicate powder (SiO2 / Na2O molar ratio = 1.98, H2O = about 20 mass %, manufactured by Tokuyama Corporation)

[0100] (4) Soda ash: Sodium carbonate powder (manufactured by Tokuyama Corporation)

[0101] Other raw materials

[0102] (5) Aggregate: Fine aggregate (JIS standard sand)

[0103] (6) Water: Ion exchange water

[0104] (Comparative Example 1)

[0105] Comparative Example 1 is a geopolymer composition produced by a manufacturing method without a carbonation treatment step of slag powder. Fly ash, slag powder, soda ash and powdered sodium silicate were weighed according to the mixing table in Table 1, put into a polyethylene bag and stirred for 3 minutes, thereby obtaining a uniformly dispersed powdered geopolymer composition. The powdered geopolymer composition and water were put into a Hobart mixer and stirred for 1 minute, 1512.4 g of aggregate was added and kneaded for 30 seconds, scraped for 15 seconds and further kneaded for 2 minutes, thereby obtaining a uniformly kneaded geopolymer composition in the form of mortar.

[0106] (Examples 1 to 5)

[0107] Examples 1 to 5 are geopolymer compositions produced by a production method including a carbonation treatment step of slag fine powder. Table 1 shows the blending amounts of fly ash, slag fine powder, soda ash, and powdered sodium silicate.

[0108] In Examples 1 to 4, as the first step, in a Hobart mixer (manufactured by Hobart Japan KK, model: MIXER N5), carbon dioxide gas (100%) is blown from a carbon dioxide gas bottle into a slurry containing slag powder and water (total amount mixed) using a silicone hose (inner diameter φ6 mm) until the slurry reaches a specified pH. The pH of the slag powder slurry during the carbonation treatment is continuously confirmed using a glass pH electrode (manufactured by AS ONE Corporation, model: AS800). The conditions of the carbonation treatment are shown in Table 2. As the second step, fly ash and alkali metal salt are added to the Hobart mixer used in the first step to which the carbonation-treated slag powder slurry is added and stirred for 1 minute, 1512.4 g of aggregate is added and kneaded for 30 seconds, and after scraping for 15 seconds, kneading is further carried out for 2 minutes, thereby obtaining a uniformly kneaded geopolymer composition in the form of mortar.

[0109] In Example 5, the same operation as in Example 4 was carried out except that a slurry containing fly ash, slag fine powder and water (total amount blended) was used in the first step.

[0110] It should be noted that the contents of various slag fine powders, AL / W (molar ratio), Si / AL (molar ratio) and (AL+W) / P that contribute to the usable time, compressive strength and 15-time impact mortar flow value (fluidity) are combined with Comparative Example 1.

[0111] [Table 1]

[0112]

[0113] ※AL / W: The molar ratio of alkali metal elements (AL) to water (W) contained in soda ash or powdered sodium silicate.

[0114] ※Si / AL: The molar ratio of silicon (Si) to alkali metal elements (AL) contained in soda ash or powdered sodium silicate.

[0115] ※(AL+W) / P: Volume ratio of the solution of soda ash, powdered sodium silicate and water to fly ash and slag powder.

[0116] [Determination of usable time]

[0117] At present, the determination method of the usable time is not established. For the ordinary Portland cement (JIS R 5210) mixed according to JIS R 5201 (11.5.1 mortar mixing), 15 impact mortar flow tests recorded in JIS R5201 are implemented every 5 minutes from just after mixing to 30 minutes, and 15 impact mortar flow tests recorded in JIS R 5201 are implemented every 10 minutes after 30 minutes, and the result is less than 130mm after 120 minutes, so it is used as a benchmark for judging whether it can be used. Therefore, a mortar flow test is implemented every 5 minutes and every 10 minutes after 30 minutes from just after mixing to 30 minutes, and the elapsed time until the flow value is less than 130mm is determined as the usable time of the geopolymer composition. The results are shown in Table 2.

[0118] [Compression strength test]

[0119] The mortars of Comparative Example 1 and Examples 1 to 5 were sealed in containers of φ (diameter) 50 mm×100 mm and sealed and cured at 20° C. and 95% RH until the prescribed ages (1 day, 7 days, and 28 days).

[0120] The mortar cured to the prescribed age (1 day, 7 days and 28 days) was subjected to a compression strength test to measure the compressive strength according to the compression strength test method described in JIS A 1108. The results are shown in Table 2. The values ​​in parentheses indicate the compressive strength ratio compared with Comparative Example 1.

[0121] [Table 2]

[0122]

[0123] As shown in Table 2, in Comparative Example 1, the usable time was 15 minutes, and a sufficient usable time for construction work at a construction site could not be obtained.

[0124] In Examples 1 to 5, the usable time was significantly extended compared to Comparative Example 1. In particular, in Examples 3 to 5, a usable time of more than 1 hour was obtained, which was sufficient to ensure the actual on-site working time, and the strength performance was 80% or more compared to the system using untreated slag fine powder.

Claims

1. A method for producing a geopolymer composition, which is a method for producing a geopolymer composition comprising slag fine powder, fly ash and an alkali metal salt, It has the following processes: (1) In the first step, carbon dioxide gas is blown into a slurry containing slag powder and water to adjust the pH of the slurry to 6.0 to 12.0, thereby carbonating the slag powder; and a second step of mixing the slurry containing the carbonation-treated slag fine powder obtained in the first step, fly ash and an alkali metal salt, Alternatively, it has the following steps: (2) In the first step, carbon dioxide gas is blown into a slurry containing slag powder, fly ash and water to adjust the pH of the slurry to 6.0 to 12.0, thereby carbonating the slag powder; In the second step, the slurry containing the carbonation-treated slag fine powder obtained in the first step is mixed with an alkali metal salt.

2. The method for producing a geopolymer composition according to claim 1, characterized in that: In the first step, the pH of the slurry is set to 6.5 to 7.

5.

3. A method for producing a geopolymer solidified product, wherein: After the geopolymer composition is obtained by the production method according to claim 1 or 2, the obtained geopolymer composition is cured at a temperature range of 5°C to 90°C.

4. The method for producing a geopolymer solidified material according to claim 3, wherein: The geopolymer composition is cured at a temperature ranging from 5°C to 35°C.

5. The method for producing a geopolymer composition according to claim 1 or 2, characterized in that: The alkali metal salt comprises alkali metal silicate powder and alkali metal carbonate powder.

6. The method for producing a geopolymer composition according to claim 5, characterized in that: The alkali metal silicate powder is sodium silicate powder.

7. The method for producing a geopolymer composition according to claim 5, characterized in that: The alkali metal carbonate powder is sodium carbonate powder.

8. The method for producing a geopolymer composition according to claim 5, characterized in that: The alkali metal silicate powder is sodium silicate powder, and the alkali metal carbonate powder is sodium carbonate powder.

9. The method for producing a geopolymer composition according to claim 5, characterized in that: The treatments of the first step and the second step are performed at a construction site where the geopolymer composition is cured.

Citation Information

Patent Citations

  • Geopolymer composition, manufacturing method thereof, and repair method for concrete structure

    JP2021054678A

Cited By

  • Method and system for preparing geopolymer by using CO2

    CN121735585A